UNDERSTANDING AND FOSTERING INTERACTION IN THREADED DISCUSSION - Williams, Robert S.; Humphrey, Rachel (Online Learning, 2007)
This study (N=2,826 postings from 92 participants) examines the phenomenon of interactivity in asynchronous computer-mediated communication (ACMC), also known as threaded discussion, in the context of master’s level Teaching English as a Second Language (MATESL) and Teaching English as a Foreign Language (MATEFL) courses. The study, which is grounded in a group of interrelated pragmatic, learning community, and pedagogical theories, attempts to determine when and under what conditions interactivity, here defined as a response to a previous posting, occurs. We focus on conditions that are present in interactive threaded discussions, those with low rates of serial monologuism and high rates of participant uptake. Taking interactivity as the dependent variable, we test a number of properties of individual ACMC postings to determine their relationships to interactivity. These variables include biographical properties of the writers (gender and first language (L1), role in the course) and a group of individual ACM posting properties, such the content of the posting (course related, phatic, both), whether or not the posting is interactive, the length of the posting, its intended audience, and whether or not the posting contains indicators of social presence (use of social speech, humor, naming, and more), face-threatening speech acts, and direct questions. Data used in the study were collected from ACMC, part of a web-based graduate introduction to second language acquisition and research methods courses. Participants in the courses were from various L1 backgrounds, including American English, Polish, Korean, and Arabic. Among our findings is that while social presence markers do not predict interactivity, there does seem to be some relationship between indicators of social presence and the quality of interaction.